NCMP-03. AN UNUSUAL CASE OF NEUROBLASTOMA ASSOCIATED OMS: HIGH RISK DISEASE REQUIRING IMMUNOTHERAPY. (11th November 2019) - Stiefel, Jessica; Khakoo, Yasmin; Basu, Ellen; Meyer, Rina; Kaur, Gurcharanjeet
Abstract: INTRODUCTION: Opsoclonus-myoclonus-ataxia syndrome (OMS) is a rare paraneoplastic syndrome (PNS) typically associated with low-risk pediatric neuroblastoma (NB). Overall survival is excellent but patients are at risk for long-term neurologic sequelae. As with many PNS, the etiology of NB-associated OMS is thought to be immune mediated and patients are managed with immunosuppressive therapy. The use of other immunotherapy such as checkpoint inhibitors for advanced stage cancers has been associated with sporadic reports of the development of PNS. We report a case of a child with NB-associated OMS who received anti-GD2 antibody immunotherapy for advanced relapsed NB without exacerbation of OMS. While the mechanism of action of anti-GD2 is unique, this case demonstrates that further study is required to understand which patients are at risk for PNS development/flare during therapy for advanced stage cancers. CASE: Our patient presented at 16 months of age with acute onset of tremors, irritability and ataxia and was diagnosed with OMS; at that time, evaluation revealed intermediate risk stage 4 neuroblastoma which was treated with 4 cycles of chemotherapy with complete response. His OMS was managed initially with high dose dexamethasone, followed by monthly IVIG, ACTH and rituximab with improvement in neurologic symptoms. The patient developed NB relapse (stage 4) 18 months after completion of initial chemotherapy and received chemotherapy and anti-GD2 antibody immunotherapy. Through this second course of therapy he continued to wean his immunosuppressive anti-OMS therapy without flare of his neurologic symptoms. DISCUSSION: We present an unusual case of a child with NB-associated OMS whose OMS symptoms did not flare despite the use of immunotherapy to treat relapsed stage 4 disease. CONCLUSION: While immunosuppression is used to treat OMS and other paraneoplastic syndromes, the use of immunotherapy to treat the underlying malignancy may be tolerated. Further study is needed.